B‐Doping‐Enhanced Stability of Phosphorene/Graphene Heterostructures. Issue 4 (21st December 2018) - Zhu, Jiajie; Gandi, Appala Naidu; Gu, Mu
Abstract: Two‐dimensional material heterostructures show large surface area and unusual electronic properties, being used in nanoelectronic devices, energy storage devices, and sensors. Doping can improve stability of the heterostructures. Structural and electronic properties of B–doped phosphorene/graphene heterostructures are studied using first‐principles calculations. B doping in phosphorene enhances the interlayer charge transfer from phosphorene to graphene. Importantly, B doping creates strong chemical bonding at the interface, which improves stability of phosphorene/graphene heterostructures. The band gap is opened up to 0.53 eV by B doping. Abstract : B doping in phosphorene creates an interlayer B‐P bond for the BP3 /BC3 heterostructure as compared to the van der Waals interaction for P4 /BC3 . The band gaps of the heterostructures are opened up to 0.53 eV. B doping improves the applications of the phosphorene‐based heterostructures in nanoelectronic devices and energy storage devices. .